Difference between revisions of "009A Sample Midterm 3, Problem 5"

From Math Wiki
Jump to navigation Jump to search
 
(One intermediate revision by the same user not shown)
Line 1: Line 1:
 
<span class="exam"> Find the derivatives of the following functions. Do not simplify.
 
<span class="exam"> Find the derivatives of the following functions. Do not simplify.
  
<span class="exam">(a)&nbsp; <math style="vertical-align: -16px">f(x)=\frac{(3x-5)(-x^{-2}+4x)}{x^{\frac{4}{5}}}</math>
+
<span class="exam">(a)&nbsp; <math style="vertical-align: -16px">f(x)=\sin\bigg(\frac{x^{-3}}{e^{-x}}\bigg)</math>
  
<span class="exam">(b)&nbsp; <math>g(x)=\sqrt{x}+\frac{1}{\sqrt{x}}+\sqrt{\pi}</math>&nbsp; for &nbsp;<math style="vertical-align: 0px">x>0.</math>
+
<span class="exam">(b)&nbsp; <math style="vertical-align: -18px">g(x)=\sqrt{\frac{x^2+2}{x^2+4}}</math>
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
+
<span class="exam">(c)&nbsp; <math style="vertical-align: -6px">h(x)=(x+\cos^2x)^8</math>
!Foundations: &nbsp;
 
|-
 
|'''1.''' '''Product Rule'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(f(x)g(x))=f(x)g'(x)+f'(x)g(x)</math>
 
|-
 
|'''2.''' '''Quotient Rule'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}\bigg(\frac{f(x)}{g(x)}\bigg)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}</math>
 
|-
 
|'''3.''' '''Power Rule'''
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(x^n)=nx^{n-1}</math>
 
|}
 
  
 +
<hr>
 +
[[009A Sample Midterm 3, Problem 5 Solution|'''<u>Solution</u>''']]
  
'''Solution:'''
 
  
'''(a)'''
+
[[009A Sample Midterm 3, Problem 5 Detailed Solution|'''<u>Detailed Solution</u>''']]
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|Using the Quotient Rule, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>f'(x)=\frac{x^{\frac{4}{5}}((3x-5)(-x^{-2}+4x))'-(3x-5)(-x^{-2}+4x)(x^{\frac{4}{5}})'}{(x^{\frac{4}{5}})^2}.</math>
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we use the Product Rule to get
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{f'(x)} & = & \displaystyle{\frac{x^{\frac{4}{5}}((3x-5)(-x^{-2}+4x))'-(3x-5)(-x^{-2}+4x)(x^{\frac{4}{5}})'}{(x^{\frac{4}{5}})^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{x^{\frac{4}{5}}[(3x-5)(-x^{-2}+4x)'+(3x-5)'(-x^{-2}+4x)]-(3x-5)(-x^{-2}+4x)(\frac{4}{5}x^{-\frac{1}{5}})}{(x^{\frac{4}{5}})^2}}\\
 
&&\\
 
& = & \displaystyle{\frac{x^{\frac{4}{5}}[(3x-5)(2x^{-3}+4)+(3)(-x^{-2}+4x)]-(3x-5)(-x^{-2}+4x)(\frac{4}{5}x^{-\frac{1}{5}})}{(x^{\frac{4}{5}})^2}.}
 
\end{array}</math>
 
|}
 
  
'''(b)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>g'(x)=(\sqrt{x})'+\bigg(\frac{1}{\sqrt{x}}\bigg)'+(\sqrt{\pi})'.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Since &nbsp;<math style="vertical-align: 0px">\pi</math>&nbsp; is a constant, &nbsp;<math style="vertical-align: -3px">\sqrt{\pi}</math>&nbsp; is also a constant.
 
|-
 
|Hence,
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>(\sqrt{\pi})'=0.</math>
 
|-
 
|Therefore, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{g'(x)} & = & \displaystyle{(\sqrt{x})'+\bigg(\frac{1}{\sqrt{x}}\bigg)'+(\sqrt{\pi})'}\\
 
&&\\
 
& = & \displaystyle{\frac{1}{2}x^{-\frac{1}{2}}+-\frac{1}{2}x^{-\frac{3}{2}}+0}\\
 
&&\\
 
& = & \displaystyle{\frac{1}{2}x^{-\frac{1}{2}}+-\frac{1}{2}x^{-\frac{3}{2}}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math>f'(x)=\frac{x^{\frac{4}{5}}[(3x-5)(2x^{-3}+4)+(3)(-x^{-2}+4x)]-(3x-5)(-x^{-2}+4x)(\frac{4}{5}x^{-\frac{1}{5}})}{(x^{\frac{4}{5}})^2}</math>
 
|-
 
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math>g'(x)=\frac{1}{2}x^{-\frac{1}{2}}+-\frac{1}{2}x^{-\frac{3}{2}}</math>
 
|}
 
 
[[009A_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 14:25, 9 November 2017

Find the derivatives of the following functions. Do not simplify.

(a) 

(b) 

(c) 


Solution


Detailed Solution


Return to Sample Exam